2019
DOI: 10.1177/1060028019842656
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacist Impact Within an Interdisciplinary Inpatient Heart Failure Consult Service

Abstract: Background: Heart failure (HF) is highly prevalent in the Veterans Affairs (VA) health care system and the leading cause of hospital discharges in the VA. Despite guideline-specific recommendations of drug therapy, many patients are not on optimal medication regimens. Objective: To examine and quantify pharmacist impact in an interdisciplinary HF consult (IC) service on increasing use of guideline-directed medical therapy (GDMT). The 30-day readmission rates before and after the implementation of an IC service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…They gave proper education and counseling about contraindications, intolerance, or other reasons to HF team in collaboration with the patients and caregivers for not utilizing proper therapies [41]. problems and provide comprehensive, and timely responses to drug information requests as well as they document the source of scientifically valid information and advice regarding the safe, appropriate, and costeffective use of medicines and develop, review, and evaluates clinical guidelines for medications used in stated management protocol with GDMTs according to evidence, compliance with prescription during hospitalization and delivery of adequate patient education regarding medication use and follow-up, thereby improving the outcome of patients with HF [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…They gave proper education and counseling about contraindications, intolerance, or other reasons to HF team in collaboration with the patients and caregivers for not utilizing proper therapies [41]. problems and provide comprehensive, and timely responses to drug information requests as well as they document the source of scientifically valid information and advice regarding the safe, appropriate, and costeffective use of medicines and develop, review, and evaluates clinical guidelines for medications used in stated management protocol with GDMTs according to evidence, compliance with prescription during hospitalization and delivery of adequate patient education regarding medication use and follow-up, thereby improving the outcome of patients with HF [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies investigating the effect of pharmacists during in-person HF visits have demonstrated improvements in patients' selfmaintenance, self-management, and self-confidence behaviors, increased use in guideline-directed medical therapy, shorter time to necessary follow-up visits, and reduction in 30day mortality and hospital readmission. [8][9][10] Another method of delivering pharmacy services that has been shown to demonstrate a positive impact on patient care is telehealth. 7 In the outpatient setting, telehealth services allow the patient to have more accessibility to their provider by reducing the burden of in-person office visits.…”
Section: Introductionmentioning
confidence: 99%